Fundamental understanding of re-dispersion of cobalt on supported model Fischer-Tropsch catalysts - Hauman, Magdalena Maria (Department of Chemical Engineering, 2015)
The aim of this study was to investigate how the catalytically active material may redisperse during consecutive oxidation-reduction steps (OROR) for a model supported-cobalt catalyst to give insight into the regeneration process of a spent supported-cobalt FTS catalyst.